Na poti k etnološkim pogledom in podobam - Slavec Gradišnik, Ingrid (Traditiones (Ljubljana), 2008)
This article presents the background, implementation, and some findings of the research project Etnološki pogledi in podobe med 19. in 21. stoletjem (Ethnological Perspectives and Images between the Nineteenth and Twenty-First Centuries), which are to be understood as a study of the possibilities to design a representative work on culture and cultural processes in Slovenia. From the end of the nineteenth century onwards, the images of culture (or culture in the broadest ethnological meaning), venues of everyday life, needs, communication modes, values, identity patterns, and so on have changed radically; at the same time, this has been a period in which modern ethnology and folklore studies have matured from local studies and philology into a scholarly discipline. Restriction to this period has marked the design of the project, which has been guided by the ambition to know more about the intersections and crossroads between empiric perceivable elements and scholarly interventions in them, to comprehend the "views" of the reality studied, and to reveal "images" connected with it.
Keywords: ethnology; etnologija; history; zgodovina; metodologija; scientific method; znanstveno raziskovanje; Slovenia; Slovenija